1994
DOI: 10.1007/bf00627737
|View full text |Cite
|
Sign up to set email alerts
|

Predator detection and avoidance by lotic mayfly nymphs of different size

Abstract: We studied antipredatory responses of lotic mayfly (Baetis) nymphs in a factorial experiment with four levels of fish presence: (1) a freely foraging fish (the European minnow,Phoxinus phoxinus), (2) a constrained fish, (3) water from a fish stream, (4) water from a fishless stream. LargeBaetis nymphs drifted mainly during night-time in treatments involving either the chemical or actual presence of fish, whereas no diel periodicity was observed when the water was not conditioned with fish odour. The response w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…Responses to live predators as used in this study may dier to that of predator cues only (e.g. Tikkanen et al 1994Tikkanen et al , 1996. Nevertheless Andersson et al (1986), in a unreplicated experiment conducted in the StampenbaÈ cken stream, found that G. pulex drift Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Responses to live predators as used in this study may dier to that of predator cues only (e.g. Tikkanen et al 1994Tikkanen et al , 1996. Nevertheless Andersson et al (1986), in a unreplicated experiment conducted in the StampenbaÈ cken stream, found that G. pulex drift Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Bluegills (Lepomis macrochirus) and striped shiners (Luxilus chrysocephalus) are predatory ®sh that forage from the water column and substrates surface. Visual cues are an important component of the foraging behavior of bluegills (Werner and Hall 1974;O'Brien et al 1976;Gerking 1994), and many cyprinids are active during the day, presumably using visual cues to detect prey (Tikkanen et al 1994;Moyle and Cech 1996). Twolined salamanders (Eurycea bislineata) are relatively small benthic predators that prey on a variety of invertebrates, including amphipods (Petranka 1984).…”
Section: Study Animalsmentioning
confidence: 99%
“…Intermediate hosts most often rely on various sensory modalities, such as vision, olfaction, and sound and vibration detection, to locate and avoid predators (Tikkanen et al, 1994;Wudkevich et al, 1997;Abjörnsson et al, 2000;Popper et al, 2001). Modifying more than one sensory modality may then increase the vulnerability of infected intermediate hosts to predation by final hosts.…”
Section: Adaptive Explanations For Multidimensionality In Pipasmentioning
confidence: 99%